2016
DOI: 10.3390/ijerph13111094
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Intervention for Increasing Clinical Nurses’ Knowledge of HIV/AIDS-Related Occupational Safety

Abstract: Background: Approximately 35 new HIV (Human Immunodeficiency Virus, HIV) cases and at least 1000 serious infections are transmitted annually to health care workers. In China, HIV prevalence is increasing and nursing personnel are encountering these individuals more than in the past. Contaminated needle-stick injuries represent a significant occupational burden for nurses. Evidence suggests that nurses in China may not fully understand HIV/AIDS (Acquired immunodeficiency syndrome, AIDS) and HIV-related occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
2
3
0
1
Order By: Relevance
“…This study established that the respondents considered to be knowledgeable in the Standard precautions had higher odds of being compliant with the Standard Precautions compared to those considered not knowledgeable (AOR 1.9, CI1.1-3.6). These findings are in conformity with the results posted by [18] which essentially means the educational program addressed some knowledge gaps identified in the Standard Precautions. However, another study [19] demonstrated a contrary result which infers that there could be other factors other than knowledge that determines of compliance to the Standard Precautions.…”
Section: The Self-reported Compliance With the Standard Precautionssupporting
confidence: 79%
“…This study established that the respondents considered to be knowledgeable in the Standard precautions had higher odds of being compliant with the Standard Precautions compared to those considered not knowledgeable (AOR 1.9, CI1.1-3.6). These findings are in conformity with the results posted by [18] which essentially means the educational program addressed some knowledge gaps identified in the Standard Precautions. However, another study [19] demonstrated a contrary result which infers that there could be other factors other than knowledge that determines of compliance to the Standard Precautions.…”
Section: The Self-reported Compliance With the Standard Precautionssupporting
confidence: 79%
“…Exposures occur under a wide variety of scenarios, as evidenced by various studies (1)(2)(3)(4). The rate of human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) infections among health care workers that are caused by sharps injuries is higher in the Caribbean and Latin America than in other regions of the world (5).…”
mentioning
confidence: 99%
“…When divided according to occupation, 25% of nurses and 8% of personnel gave the correct response. Studies show that especially nurses and laboratory employees encounter contact with blood and body fluids with needlestick accidents; however, when questions about the transmission rate due to being stuck by an infected patient's needle were asked, only a very small portion gave the correct answer (13,14). Studies, similarly, showed lack of information about occupational diseases and work accidents among health personnel (15,16), and that adding these topics to educational meetings during working life and even informing individuals who attend routine check-ups in occupational health clinics with special booklets/brochures will be beneficial.…”
Section: Discussionmentioning
confidence: 99%